Effect of sodium lactate /sodium diacetate in combination with sodium nitrite on physiochemical, microbial properties and sensory evaluation of cow sausage - Sedghi, Habib; Sani, Ali Mohamadi; Najafi, Masood Najaf; Shariati, Mohammad Ali (Potravinarstvo Slovak Journal of Food Sciences, 2014)
Sodium nitrite has been always considered as one of the common additives due to its antibacterial effects on Clostridium botulinum and meat products’ color, however it produces cancer creating nitrosamine. Recently, organic acids and their salts such as lactates have been employed as antimicrobial compounds. Lactates also improve organileptic properties including color, texture and taste and antioxidant properties. Sodium lactate causes to more reduction of anaerobic spore former bacteria than nitrite, inhibits botulin produced by Clostridium botulinum. Sodium lactate produces a permanent reddish pink color through reduction of deoxymygloboline and producing deoxymyoglobuline. In this study, the decrease of sodium nitrite amount from 120ppm to 15ppm by adding sodium lactate / sodium diacetate led to achieve an acceptable product. The best results revealed through adding 3.0625% of sodium lactate / sodium diacetate in combination with 30ppm sodium nitrite. Results also exhibited more reduction of pathogens’ growth than nitrite, enhanced flavor slightly, but unable to produce reddish pink color as produced by nitrite. Results also exhibited that sodium lactate / diacetate cause to retard in microbial growth, reducing chemical change, enhance sensory properties, partially improvement in taste and texture. Although inappropriate color demonstrated sodium lactate / diacetate’s inability in red pink color production in 4th sample (contains 15 ppm nitrite), its synergy effect in combination with sodium nitrite on nitroso myoglobuline production has been proven, led to sodium nitrite reduction in sausages.